(untitled) («CONTEMPORARY TECHNOLOGIES OF COMPUTATIONAL LINGUISTICS», 2024)
Corpus linguistics is a branch of computational linguistics that develops general principles for the construction and use of linguistic corpora using computer technology. The corpus approach as a method of linguistic research is focused on applied language learning. At present, all modern linguistic researchers and compilers of dictionaries are increasingly using voluminous text corpora. The following describes ways to use corpora, in particular, based on the representative volume of the corpus, the possibility of teaching Russian grammar and creating a modern word-building dictionary of the Russian language. The multifaceted application of corpora testifies to the significant role of corpus linguistics and its presentation as a tool for modern linguistic research.